The effects of remifentanil used during cesarean section on oxidative stress markers in correlation with maternal hemodynamics and neonatal outcome: a randomized controlled trial - Kutlesic,Marija S. (2019)
Abstract Background and objective: Remifentanil is used to attenuate maternal hemodynamic response to intubation and surgical stress during Induction-Delivery period of cesarean section. The goal was to compare the effects of two remifentanil dosing regimens on oxidative stress level, in correlation with its hemodynamic and neonatal effects. Methods: Fifty-one patients, 17 per group, enrolled for elective cesarean section were randomly divided by computer-generated codes into three parallel groups: (A) patients received a 1 µg.kg-1 remifentanil bolus immediately before induction, followed by 0.15 µg.kg-1.min-1 infusion, that was stopped after skin incision; (B) patients received a 1 µg.kg-1 remifentanil bolus immediately before induction; (C) (control), patients did not receive remifentanil until delivery. Maternal venous blood samples were taken at basal time, at extraction and 30 minutes after the end of operation for spectrophotometrical determination of malondialdehyde and advanced oxidation protein products concentration. The same was conducted for umbilical venous sample. Results: Systolic blood pressure and heart rate remained significantly lower in group A compared to B and C during entire Induction-Delivery period (p < 0.001, p = 0.02 after intubation; p = 0.006, p = 0.03 after skin incision; p = 0.029, p = 0.04 after extraction; respectively). Malondialdehyde concentration was lower at time of extraction in maternal blood in group A compared to B and C (p = 0.026). All neonatal Apgar scores were ≥ 8 and umbilical acid-base values within normal range. Conclusions: The remifentanil dosing regimen applied in group A significantly attenuated lipid peroxidation and maternal hemodynamic response during entire I-D period, without compromising neonatal outcome.